An optimization model to maximize energy generation in short-term hydropower unit commitment using efficiency points. (February 2021) - Daadaa, Maissa; Séguin, Sara; Demeester, Kenjy; Anjos, Miguel F.
Highlights: A novel optimization model to maximize energy for short-term hydropower unit commitment is proposed. A MILP formulation based on the efficiency curves is established. The optimized solutions can be directly implemented in practice. A real case study in Canada shows benefits of optimal solutions compared to historical decisions. Abstract: This paper presents a linear mixed-integer formulation to solve the short-term hydropower unit commitment problem. It uses the pair of maximum efficiency points of water discharge and the power produced at the maximum storage for all possible combinations of turbines. The goal is to maximize total energy production for all periods. The objective function is calculated using the correction between the power produced at the current volume and the maximum storage and penalizes unit start-ups. Constraints on the maximum number of turbine changes are imposed to find a viable solution. Computational results are reported for 65 instances with two powerhouses of five turbines each located in the Saguenay-Lac-St-Jean region of the province of Quebec in Canada.